A perspective of immunotherapy for acute myeloid leukemia: Current advances and challenges - Chen, Ying; Wang, Jishi; Zhang, Fengqi; Liu, Ping (Frontiers in Pharmacology, 2023)
The underlying pathogenic mechanisms of acute myeloid leukemia (AML) have been studied extensively in the past few years, and considerable progress has been made in the understanding the disease. However, both of drug resistance in chemotherapy and relapse remain the principal obstacles to successful treatment. Because of acute and long-term side effects commonly induced by conventional cytotoxic chemotherapy, consolidation chemotherapy is not feasible, especially for elderly patients, which has attracted a growing body of research to attempt to tackle this problem. Immunotherapies for AML, including immune checkpoint inhibitors, monoclonal antibodies, dendritic cell (DC) vaccines, as well as chimeric antibody receptor-engineered T cells (CAR-T) have been developed in recent years. Our review presents the recent progress in immunotherapy for the treatment of AML and discusses effective therapies that have the most potential and major challenges.